Risk of catecholamine crisis in patients undergoing resection of unsuspected pheochromocytoma - Gina Song (International Brazilian Journal of Urology, 2011)
PURPOSE: To report the risk of catecholamine crisis in patients undergoing resection of unsuspected pheochromocytoma. MATERIALS AND METHODS: Over a four-year period, we retrospectively identified four patients who underwent resection of adrenal pheochromocytoma in whom the diagnosis was unsuspected based on preoperative clinical, biochemical, and imaging evaluation. RESULTS: None of the patients exhibited preoperative clinical features of catecholamine excess. Preoperative biochemical screening in two patients was normal. CT scan performed in all patients demonstrated a nonspecific enhancing adrenal mass. During surgical resection of the adrenal mass, hemodynamic instability was observed in two of four patients, and one of these two patients also suffered a myocardial infarct. CONCLUSION: Both surgeons and radiologists should maintain a high index of suspicion for pheochromocytoma, as the tumor can be asymptomatic, biochemically negative, and have nonspecific imaging features. Resection of such unsuspected pheochromocytomas carries a substantial risk of intraoperative hemodynamic instability.